Gestion des risques en responsabilité professionnelle des ingénieurs et des architectes - Arsenault, Laurent (Assurances)

(untitled) (HEC Montréal, 1993)
A thorough analysis of the technical, commercial and legal risks facing today's professional engineer or architect forms the basis for the management of these risks and the minimization of their consequences. Prevention through quality control, astute insurance coverage selection and the promotion of alternate dispute resolution techniques are essential preventive risk management steps to be taken. Claims management approach and the relationship with the client during the claims resolution process are equally important in minimizing risks.